If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4r + -8) = 36 Reorder the terms: 3(-8 + 4r) = 36 (-8 * 3 + 4r * 3) = 36 (-24 + 12r) = 36 Solving -24 + 12r = 36 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 12r = 36 + 24 Combine like terms: -24 + 24 = 0 0 + 12r = 36 + 24 12r = 36 + 24 Combine like terms: 36 + 24 = 60 12r = 60 Divide each side by '12'. r = 5 Simplifying r = 5
| 4=6x+10 | | 10+3=6x+5 | | 32=-16t^2+p | | 25x^2+4=-20x | | h=-16t^2+p | | (y-7)=(y+6) | | -1.5=12y | | y^2+y+2=0 | | 6-7s-4-s= | | 5x+24-7x+14=x+5 | | 4(3n-1)=(8n+3)+3 | | (6x-12)+72+9x=180 | | 9x+6=x+5 | | (7x^4+2)*(7x^4+2)= | | -4+23=m-8 | | -9x^2+8x-3=-200 | | m^2+2mn+n^2-16p^2=0 | | a^2+49=14a | | 6x^2-18x-108=-9 | | 3xy/x | | 3b-13=-5b+3 | | 43-4x= | | Y-160=40(x-1) | | (d-1)+4=-2d | | z^2-22+10z=0 | | 6x-47= | | 9r-17=-4r+8 | | 6x^2-12x-80=0 | | 87.5h-62.5=2 | | 2(5x-4)=ax | | 7x+11=5x+25 | | -7(9+5h)+2= |